Design and Investigation of Disk Patch Antenna with Quad C-Slots for Multiband Operations. (19th November 2014) - Ansari, J. A.; Verma, Sapna; Singh, Ashish
Abstract : An investigation into the design and fabrication of multiband disk patch antenna with symmetrically quad C-slots is presented in this paper. The proposed antenna shows multiband resonance frequencies which highly depend on substrate thickness, dielectric constant, and radius of the disk patch. By incorporating two pairs of C-slots in optimum geometry on the radiating patch, the proposed antenna operates between 2 and 12 GHz at different frequency bands centered at 2.27, 7.505, 9.34, 10.33, and 11.61 GHz. The other antenna parameters are studied like gain, antenna efficiency, and radiation pattern. The proposed antenna may find applications in S-, C-, and X-band. The results are carried out with the aid of HFSS and MOM-based IE3D simulator. The measured and simulated results are in good agreement with each other.